Odpowiedzi

Najlepsza Odpowiedź!
2010-01-14T14:08:58+01:00
A) x² = 2² + 4²
x² = 4 + 16
x² = 20
x = √20 (pierwiastek z 20)
x≈4,5

b) x² + (2,7)² = (3,5)²
x² + 7,29 = 12,25
x² = 4,96
x = √4,96
x=2,2

c) x² = (1,5)² + (0,5)²
x² = 2,25 + 0,25
x² = 2,5
x = √2,5
x = 1,6

d) x² = (1,5)² + (2,8)²
x² = 2,25 + 7,84
x² = 10,09
x = √10,09
x = 3,2

e) x² + (2,3)² = 4²
x² + 5,29 = 16
x² = 10,71
x= √10,71
x=3,3

f) x² + (0,6)² = 1²
x² + 0,36 = 1
x² = 0,64
x= √0,64
x=0,8
31 4 31
  • Roma
  • Community Manager
2010-01-14T14:12:54+01:00
A)
x² = 2² + 4²
x² = 4 + 16
x² = 20
x = √20
x ≈ 4,5

b)
x² = (3,5)² - (2,7)²
x² = 12,25 - 7,29
x² = 4,96
x ≈ 2,2

c)
x² = (1,5)² + (0,5)²
x² = 2,25 + 0,25
x² = 2,5
x ≈ 1,6

d)
x² = (1,5)² + (2,8)²
x² = 2,25 + 7,84
x² = 10,09
x ≈ 3,2

e)
x² = 4² - (2,3)²
x² = 16 - 5,29
x² = 10,71
x ≈ 3,3

f)
x² = 1² - (0,6)²
x² = 1 - 0,36
x² = 0,64
x = 0,8
16 4 16